Phytochemical Profile, α-Glucosidase, and α-Amylase Inhibition Potential and Toxicity Evaluation of Extracts from Citrus aurantium (L) Peel, a Valuable By-Product from Northeastern Morocco - Ouijdane Benayad (MDPI AG, 2021)
Due to the high volume of peel produced, Citrus by-product processing could be a significant source of phenolic compounds, in addition to essential oil. Citrus fruit residues, which are usually dumped as waste in the environment, could be used as a source of nutraceuticals. Citrus aurantium (L), also known as sour or bitter orange, is a member of the Rutaceae family and is the result of interspecific hybridization between Citrus reticulata and Citrus maxima. The purpose of this study is to chemically and biologically evaluate the peel of C. aurantium, which is considered a solid waste destined for abandonment. To achieve more complete extraction of the phytochemicals, we used a sequential extraction process with Soxhlet using the increasing polarity of solvents (i.e., cyclohexane, chloroform, ethyl acetate, acetone, and ethanol–water mixture). Essential oil (EO) from the Citrus peel, which was present at 1.12%, was also prepared by hydrodistillation for comparison. Various phytochemical assays were used to determine the qualitative chemical composition, which was subsequently characterized using GC-MS and HPLC-DAD. The inhibitory effects of C. aurantium peel extract on two enzymes, intestinal α-glucosidase and pancreatic α-amylase, were measured in vitro to determine their potential hypoglycemic and antidiabetic actions. Each extract had a significantly different phytochemical composition. According to GC-MS analyses, which allow the identification of 19 compounds, d-limonene is the most abundant compound in both EO and cyclohexane extract, at 35.17% and 36.15% (w/w). This comparison with hydrodistillation shows the value of the sequential process in extracting this valuable terpene in large quantities while also allowing for the subsequent extraction of other bioactive substances. On the contrary, linoleic acid is abundant (54.35% (w/w)) in ethyl acetate extract (EAE) with a lower amount of d-limonene. HPLC-DAD analysis allows the identification of 11 phytochemicals, with naringenin being the most abundant flavanone, detected in acetone extract (ACE) (23.94% (w/w)), ethanol–water extract mixture (EWE) (28.71% (w/w)), and chloroform extract (CFE) (30.20% (w/w)). Several extracts significantly inhibited α-amylase and/or α-glycosidase in vitro. At a dose of 332 g/mL, ACE, CFE, and EWE inhibited the two enzymes by approximately 98%. There were strong significant correlations between naringenin and α-glucosidase inhibition and between gallic acid and α-amylase inhibition. Molecular docking experiments further verified this. Finally, oral administration of C. aurantium extracts at a dose of 2000 mg/kg did not cause any effect on mice mortality or signs of acute toxicity, indicating that it is non-toxic at these doses. These findings suggest that C. aurantium peels could be a valuable by-product by providing a rich source of non-toxic phytoconstituents, particularly those with potential antidiabetic action that needs to be confirmed in vivo.